1980
DOI: 10.1038/icb.1980.66
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Xylitol on the Ability of Rat Caecal Flora to Metabolise Xylitol

Abstract: Summary. The effect of dietary xyiitol on the ability ofthe rat caeca! flora lo metabolise xylitol was investigated. Xylitol metabolism in micro-organisms has generally been assessed in terms ofpH change and acid production wbich are often insensitive in demonstrating low rates ofsubstrate utilisation. Using a rapid and sensitive radioisotopic assay. in which '*COj production from lU-'^Cl xylitol was measured, it was possible to show that the caecal microflora obtained from rats can metabolise xylitol. This ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The higher cecum percentages observed in the xylitol group indicate the presence of a simpler flora (19,45). A shift to an increased fecal proportion of grampositive versus gram-negative organisms has been described by others for animals receiving xylitol (22,33,35). In fact, we have seen the disappearance of nonlactose fermentors from the stools of mice receiving xylitol in previous experiments (39a).…”
Section: -Xylitol (N-14)supporting
confidence: 77%
See 1 more Smart Citation
“…The higher cecum percentages observed in the xylitol group indicate the presence of a simpler flora (19,45). A shift to an increased fecal proportion of grampositive versus gram-negative organisms has been described by others for animals receiving xylitol (22,33,35). In fact, we have seen the disappearance of nonlactose fermentors from the stools of mice receiving xylitol in previous experiments (39a).…”
Section: -Xylitol (N-14)supporting
confidence: 77%
“…In two of these, the mice were allowed free access to drinking water that contained either D-(+)-glucose (Sigma Chemical Co., St. Louis, Mo.) (n = 10) or xylitol (Sigma) (n = 12) each at 5% (wt/vol) concentration from day 16 to day 21 and at 10% thereafter until sacrifice (22,44). The control group (n = 14) received water without carbohydrates.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism by which the constitutive fructose-PTS-negative strains arise is not known. A mutation is most unlikely, since it has been shown, in vitro and in vivo, that xylitol and its metabolites are non-mutagenic (Batzinger et al, 1977;Krishnan et al, 1980). Furthermore, it was shown (Gauthier et al, 1984) that the in vitro acquisition of the xylitol resistance phenotype was an adaptive process.…”
Section: Resultsmentioning
confidence: 96%
“…For example, cyclamate, which is currently banned in the USA, can be metabolized by gut bacteria into cyclohexylamine, which is carcinogenic [63]. Artificial sweeteners stevioside and xylitol can also be metabolized by the gut bacteria [64,65]. Several studies have demonstrated that some artificial sweeteners and emulsifiers were able to induce gut microbiome toxicity with potential gut microbiota-related health consequences.…”
Section: Artificial Sweetenersmentioning
confidence: 99%